Análisis multifractal de la variabilidad espacial de la conductividad hidráulica en un suelo estratificado - Posadas, Adolfo (2002)
Fractal and multifractal concepts are promising tools for characterizing hydraulic properties in soils. The application of one method or the other will depend on the distributión and type of variability of the properties that are being studied. The saturated hydraulic conductivity (K,) is an important soil physics parameter to establish fluid transpon in soils. The measurement of hydraulic conductivity in the laboratory has showed to be much influenced by column size. In this work we have applied multifractal theory to study the dependence of column sample size in three different soil horizons (Ap. c. and C2) and along of a transect. The multifractal parameters calculated were functions of both sample length and sample area. Smaller volumes, resulting from shorter samples or smaller area perpendicular to flow, exhibited more heterogeneous distribution and, therefore, stronger multifractal properties than larger sample volumes. The multifractal spectrum was also sensitive to the different soil horizons present in a profile. The Iarge heterogeneity, typical of surface horizons, is manifested in the wider multiracial spectrum of the Ap horizon as compared to the spectra of either Ct or C2, which show very little difference between them. On the other hand, the multifractal results as compared to semi variograms obtained using geostatistical theory; yield information in a scale range where the semi variogram did not show any relevant rcsults.© 2003 CSI. All rights reserved